Status of sleeping habits and its influence on growth and metabolism of children in Beijing: a population-based cross-sectional study - Yiren Chen; Lijun Wu; Zijun Liao; Yiying Huang; Qin Liu; Shaoli Li; Junting Liu; Xinnan Zong; Jun Tai; Fangfang Chen (BMC Public Health)
Abstract Background Sleep disturbances are associated with poor health outcomes in children. However, the sleep problems that occur in children’s growth and metabolism need to be further studied. The aim of the present study was to assess the effects of sleep habits on the growth and metabolism in school-aged children. Methods This cross-sectional study included 5832 children and adolescents aged 6–18 years from 10 primary and secondary schools in a district in Beijing between 2022 and 2023. Children’s sleep characteristics were evaluated using the Children’s Sleep Habits Questionnaire (CSHQ). Body composition, body mass index (BMI), blood pressure, fasting plasma glucose, and blood lipid levels were assessed. Results Girls had a greater rate of sleep anxiety, while boys had a greater rate of sleep-disordered breathing (SDB) across all age groups. Linear regression analysis showed that poor sleep habits were negatively correlated with height for age (HAZ) and systolic blood pressure (SBP) (β = −0.111 and − 0.459, respectively; p < 0.05). SDB was significantly associated with BMI, fat mass percentage (FMP), waist-to-height ratio (WHtR), SBP, triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) across all age groups (p < 0.05), while SDB was positively correlated with HAZ only in children aged 6–11 years (β = 0.240, p < 0.05). Logistic regression analysis showed that insufficient sleep was associated with FMP, WHtR, and overweight/obesity in children aged 6–11 years (p < 0.05). SDB was a risk factor for hypertension in children aged 12–18 years (OR = 1.847, p < 0.05). Conclusions Evaluating the multiple aspects of childhood sleep habits is crucial for improving sleep-related children’s growth and metabolism. Age differences in sleep-related growth and cardiometabolic abnormalities should be considered in preventive interventions. Our study provides new insights into age differences in the influence of sleep habits on the growth and metabolism of children.